Inhibition of antioxidant enzyme activities enhances carotenogenesis in microalga Dactylococcus dissociatus MT1 - Bouzidi, Nour Elaimane; Grama , Samir Borhane; Khelef , Aboubakeur Essedik; Yang , Duanpeng; Li , Jian (Frontiers in Bioengineering and Biotechnology, 2022)
Microalgal biotechnology has become a promising field of research for the production of valuable, sustainable and environmentally friendly byproducts, especially for carotenoids. Bulk accumulation of secondary carotenoids in microalgae are mostly induced by oxidative stress of cells. In this research, we investigated the effects of antioxidant enzyme activity inhibition on carotenogenesis in a microalga Dactylococcus dissociatus MT1. The activities of four major antioxidant enzyme families, namely superoxide dismutase (SOD), catalases (CAT), glutathione peroxydases (GPX) and ascorbate perxodases (APX), were inhibited by relevant inhibitors during the stressed cultivation of D. dissociatus to observe the effects on carotenogensis. A 91% decrease in activity was observed for CAT, comparing with controls without any inhibitors added, followed by 65%, 61% and 47% for the enzymes SOD, APX and GPX, respectively. Concomitantly, it was found that this partial inhibition had substantial influences on the accumulation of carotenoids, with the highest production levels obtained in CAT inhibition conditions and an increase of 2.6 times of carotenoid concentration observed, comparing with control cultivation conditions. We conclude that the modulation of antioxidant enzyme activities could lead to the overproduction of carotenoids in this microalgal cell culture, and we expect that this novel approach of optimizing carotenogenesis processes for D. dissociates cell cultures could be transferrable to other cell culture systems and might have an important impact on the carotenoid production industry.